Interaction does Count: A Cross-Fostering Study on Transgenerational Effects of Pre-reproductive Maternal Enrichment - Caporali, Paola; Cutuli, Debora; Gelfo, Francesca; Laricchiuta, Daniela; Foti, Francesca; De Bartolo, Paola; Angelucci, Francesco; Petrosini, Laura (Frontiers in Behavioral Neuroscience, 2015)
Pre-reproductive environmental enrichment of female rats influences sensorimotor development and spatial behavior of the offspring, possibly through the changed maternal nurturing. Nevertheless, maternal care could be not the solely responsible for changing offspring developmental trajectories. To disentangle the specific contribution to the transgenerational inheritance of pre- and post-natal factors, a cross-fostering study was performed. Female rats were reared in an enriched environment from weaning to sexual maturity, while control female rats were reared under standard conditions. Following mating with standard-reared males, all females were housed individually. Immediately after delivery, in- or cross-fostering manipulations were performed so that any foster dams received pups born to another dam of the same (in-fostering) or the opposite (cross-fostering) pre-reproductive rearing condition. In lactating dams maternal care and nesting activities were assessed, while in their male pups spatial abilities were assessed through Morris Water Maze (MWM) test at post-natal day 45. Moreover, the expression of Brain-Derived-Neurotrophic-Factor (BDNF) was evaluated in the hippocampus and frontal cortex of dams and pups at weaning. Pre-reproductive maternal environmental enrichment, followed by adoption procedures, loosened its potential in modifying maternal care and offspring developmental trajectories, as indicated by the lack of differences between in-fostered groups of dams and pups. In addition, enriched dams rearing standard pups showed the least complex maternal repertoire (the highest sniffing duration and the lowest nest quality), and their pups showed a reduced spatial learning in the MWM. Nevertheless, pre-reproductive maternal enrichment kept influencing neurotrophic pattern, with enriched dams expressing increased frontal BDNF levels (regardless of the kind of fostered pups), and their offspring expressing increased hippocampal BDNF levels. The present findings enlighten the crucial importance of the early mother-pups interactions in influencing maternal care and offspring phenotype, with the enriched dam-standard pups couple resulting in the most maladaptive encounter. Our study thus sustains that the bidirectional interactions between mother and pups are able to deeply shape offspring phenotype.